Managerial ownership and corporate diversification: a longitudinal view - Goranova, Maria; Alessandri, Todd M.; Brandes, Pamela; Dharwadkar, Ravi (Strategic Management Journal, 2007)
Abstract Strategy and finance research suggests that managerial ownership results in increased incentive alignment and therefore is negatively related to corporate diversification. Using a longitudinal approach, we develop arguments to examine whether managerial ownership is associated with subsequent changes in diversification and/or if diversification is associated with subsequent changes in ownership. The results indicate that levels of managerial ownership in one time period are not associated with subsequent changes in corporate diversification, which raises incentive alignment questions. We also find that higher levels of corporate diversification are associated with changes in managerial ownership, which suggests support for the employment risk‐reduction perspective. This study provides important reasons to reassess the longitudinal implications of the managerial ownership‐corporate diversification link from both theoretical and managerial perspectives. Copyright © 2007 John Wiley & Sons, Ltd.